Labor Mobility in the European Union. Economic and Social Implications - COJOCARU, Teodor Marian (Journal of Advanced Research in Management, 2020)
Recent economic growth has created opportunities for both domestic and foreign workers, because workers in all EU Member States directly contribute to a better functioning of economy by eliminating skills shortages and specific bottlenecks on labor market in certain European regions or states. Current studies highlight a general consensus among experts on the fundamental, global benefits of labor mobility in the EU. However, although these benefits apply at the macro level, there are always certain sectors or geographical areas where the general rules on general earnings do not apply and where costs and multiple disadvantages are concentrated .